Nucleic acid visualization assay for Middle East Respiratory Syndrome Coronavirus (MERS-CoV) by targeting the UpE and N gene. - Pei Huang; Hongli Jin; Yongkun Zhao; Entao Li; Feihu Yan; Hang Chi; Qi Wang; Qiuxue Han; Ruo Mo; Yumeng Song; Jinhao Bi; Cuicui Jiao; et al. (Public Library of Science (PLoS), 2021)
Since its first emergence in 2012, cases of infection with Middle East respiratory syndrome coronavirus (MERS-CoV) have continued to occur. At the end of January 2020, 2519 laboratory confirmed cases with a case-fatality rate of 34.3% have been reported. Approximately 84% of human cases have been reported in the tropical region of Saudi Arabia. The emergence of MERS-CoV has highlighted need for a rapid and accurate assay to triage patients with a suspected infection in a timely manner because of the lack of an approved vaccine or an effective treatment for MERS-CoV to prevent and control potential outbreaks. In this study, we present two rapid and visual nucleic acid assays that target the MERS-CoV UpE and N genes as a panel that combines reverse transcription recombinase polymerase amplification with a closed vertical flow visualization strip (RT-RPA-VF). This test panel was designed to improve the diagnostic accuracy through dual-target screening after referencing laboratory testing guidance for MERS-CoV. The limit of detection was 1.2×101 copies/μl viral RNA for the UpE assay and 1.2 copies/μl viral RNA for the N assay, with almost consistent with the sensitivity of the RT-qPCR assays. The two assays exhibited no cross-reactivity with multiple CoVs, including the bat severe acute respiratory syndrome related coronavirus (SARSr-CoV), the bat coronavirus HKU4, and the human coronaviruses 229E, OC43, HKU1 and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Furthermore, the panel does not require sophisticated equipment and provides rapid detection within 30 min. This panel displays good sensitivity and specificity and may be useful to rapidly detect MERS-CoV early during an outbreak and for disease surveillance.